2021
DOI: 10.3390/ijms22179461
|View full text |Cite
|
Sign up to set email alerts
|

Copper, Iron, Selenium and Lipo-Glycemic Dysmetabolism in Alzheimer’s Disease

Abstract: The aim of the present review is to discuss traditional hypotheses on the etiopathogenesis of Alzheimer’s disease (AD), as well as the role of metabolic-syndrome-related mechanisms in AD development with a special focus on advanced glycation end-products (AGEs) and their role in metal-induced neurodegeneration in AD. Persistent hyperglycemia along with oxidative stress results in increased protein glycation and formation of AGEs. The latter were shown to possess a wide spectrum of neurotoxic effects including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 150 publications
(157 reference statements)
1
22
0
Order By: Relevance
“…While tightly regulated levels are needed for physiological functions, overload and deficiency of these metals could lead to pathological conditions. For instance, extreme Cu and Zn levels have been associated to CVD [ 2 , 71 ], metabolic [ 149 ] and neurodegenerative diseases [ 150 , 151 ], and Se levels have been related to diabetes [ 152 ] and cardiometabolic risk [ 153 , 154 ], consistently with our data. Overall, the displayed interconnections of enriched pathways attributed to the genes interacting with metals is consistent with the hypothesis that metals can directly and indirectly influence redox-related pathways in common for human chronic diseases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While tightly regulated levels are needed for physiological functions, overload and deficiency of these metals could lead to pathological conditions. For instance, extreme Cu and Zn levels have been associated to CVD [ 2 , 71 ], metabolic [ 149 ] and neurodegenerative diseases [ 150 , 151 ], and Se levels have been related to diabetes [ 152 ] and cardiometabolic risk [ 153 , 154 ], consistently with our data. Overall, the displayed interconnections of enriched pathways attributed to the genes interacting with metals is consistent with the hypothesis that metals can directly and indirectly influence redox-related pathways in common for human chronic diseases.…”
Section: Discussionsupporting
confidence: 89%
“…Findings from the integrative biological pathway analysis are consistent with accumulated evidence supporting that non-essential metal exposures could play a role in the pathogenesis of several conditions, including CVD for Sb [ 5 , 49 ], As [ 71 ] and Cd [ 71 ], cancer and renal dysfunction for Cd [ 67 , 141 , 142 ] and As [ 67 , [143] , [144] , [145] ] and neurological disorders for As [ 146 , 147 ] and Cd [ 148 ]. However, the evidence assessing the potential health-effects of essential metals is less clear [ 2 , 4 , 71 , [149] , [150] , [151] ]. While tightly regulated levels are needed for physiological functions, overload and deficiency of these metals could lead to pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological mechanism of AD is too complex to explain it merely with Aβ and tau accumulation. Scientists have found that many pathological processes, for instance, neural inflammation ( Leng and Edison, 2021 ), oxidative stress ( Song et al, 2021 ) and metal dysregulation ( Wang et al, 2020 ; Aaseth et al, 2021 ), involved in Aβ deposition and tau hyperphosphorylation, driving the insidious progression before AD diagnosis. Currently, the involvement of iron in the early pathology of AD has been well accepted since the discovery of the link between dysregulation of brain iron homeostasis and AD pathogenesis in 1953 ( Goodman, 1953 ).…”
Section: Impact Of Iron Overload On Alzheimer’s Disease Pathologymentioning
confidence: 99%
“…Growing evidence have proved that Aβ triggers the chain events downstream in the pathological course of AD, including tau pathology. However, other processes such as neural inflammation ( Leng and Edison, 2021 ), oxidative stress ( Song et al, 2021 ), apoptosis ( Sharma et al, 2021 ), autophagy ( Zhang et al, 2021 ) and metal dysregulation ( Wang et al, 2020 ; Aaseth et al, 2021 ) are also found in AD pathology. Some of these processes are even involved in the deposition of Aβ.…”
Section: Introductionmentioning
confidence: 99%
“…•− ), but may not necessarily produce more ROS in aging [15] as damaged mitochondria are removed by autophagy [16]. Iron and ROS generation are involved in ferroptosis, a recently described form of cell death which is defined as iron-dependent regulated necrosis that is caused by massive lipid peroxidation-mediated membrane damage [17,18].…”
Section: Brain Iron Neuroinflammation and Cognitive Decline In Agingmentioning
confidence: 99%